2021
DOI: 10.17245/jdapm.2021.21.2.119
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between subjective and objective measures of anticipatory anxiety prior to extraction procedures in 8- to 12-year-old children

Abstract: Background This study assessed anticipatory dental anxiety levels among 8- to 12-year-old children based on subjective and physiological measures and their correlation. The variations in anxiety based on sex, age, temperament, and academic performance were evaluated. Methods An observational study was conducted in 60 children recruited from the waiting room over a 6-month period. The operator recorded subjective anxiety in the children using a novel visual facial anxiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…In this study, a higher activity trait was observed in younger children, while sociability was lower; both characteristics had an influence on negative behaviour and explain their lower adaptation towards dental treatment. Another study reported that 8-12-year-old children with difficult temperaments presented greater anxiety at the dental office, along with the presence of negative behaviour [22].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a higher activity trait was observed in younger children, while sociability was lower; both characteristics had an influence on negative behaviour and explain their lower adaptation towards dental treatment. Another study reported that 8-12-year-old children with difficult temperaments presented greater anxiety at the dental office, along with the presence of negative behaviour [22].…”
Section: Discussionmentioning
confidence: 99%
“…The role of preoperative anxiety in postoperative delirium remains a topic of debate. Some studies have suggested that preoperative anxiety serves as a predictive factor for postoperative delirium [14,32,33], whereas the majority of research findings indicate no significant association between preoperative anxiety and postoperative delirium in elderly patients [12][13][14]. Consequently, further investigations focusing on the relationship between preoperative anxiety and postoperative delirium are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Objective approaches encompass both indirect and direct evaluations of anxiety levels, involving the estimation of sympathoadrenal system activation and the measurement of stress hormones, respectively [29,32]. Numerous studies have demonstrated that elevated preoperative anxiety levels are associated with increased heart rate, blood pressure, plasma cortisol, and catecholamine levels, alongside a reduction in heart rate variability and oxygen saturation [29,33]. For instance, a study conducted by Balasubramaniyan N. et al in 2016 revealed that hypertensive patients undergoing dental procedures experienced significant elevations in heart rate and systolic blood pressure due to preoperative anxiety.…”
Section: Measurement Of Preoperative Anxietymentioning
confidence: 99%
“…An increase in heart rate, blood pressure,plasma cortisol andcatecholamines values, as well as a decrease in heart rate variability and oxygensaturation, were described as consequencesof higher levels of preoperative anxiety. (22)(23)(24) For instance, a study by Balasubramaniyan N. et al from 2016 investigated the association of cardiovascular alterations and anxiety in 80 hypertensive patients undergoing dental procedures. The authors demonstrated that high-level preoperative anxiety is associated with significant increases in heart rate and systolic blood pressure.…”
Section: Measurement Of Preoperative Anxietymentioning
confidence: 99%